Experimental and First‐Principles Studies of the Ternary Borides Ta3Ru5B2 and M3–xRu5+xB2 (M = Zr, Hf). Issue 19 (3rd June 2014) - Hermus, Martin; Fokwa, Boniface P. T.
Abstract: Ta3 Ru5 B2, Zr2.86(5) Ru5.14(5) B2, and Hf2.83(2) Ru5.17(2) B2 have been successfully synthesized as polycrystalline powders as well as single crystals and characterized by powder and single‐crystal X‐ray diffraction and EDX analysis. Furthermore, their electronic structures and bonding characteristics have been analyzed by DFT calculations. The three phases are isotypic and crystallize with a Ti3 Co5 B2 ‐type structure (space group P 4/ mbm ). Their electronic densities of states, which all possess a large pseudogap at the Fermi level, closely follow the rigid band model. Bonding analyses indicated that Ru–B and Ru–M (M = Zr, Hf, Ta) heteroatomic interactions are mainly responsible for their structural stability and that the homoatomic M–M interactions behave differently when connecting either two tetragonal or two pentagonal Ru prisms at the same distance. Abstract : Three new Ru‐rich ternary borides with the Ti3 Co5 B2 ‐type structure have been synthesized. Their electronic densities of states possess a large pseudogap at the Fermi level and closely follow the rigid band model. Bonding analyses indicated that Ru–B and Ru–M interactions are mainly responsible for their structural stability and that M–M interactions behave differently according to circumstance.